KAJIAN KRANIOMETRI PERSILANGAN SAPI BELGIAN BLUE DENGAN SAPI PERANAKAN ONGOLE DI JAWA BARAT - Aditya, Natasha Ramanda; Dudi, Dudi; Arifin, Johar (Faculty of Animal Husbandry, Universitas Padjadjaran, 2024)
Research on the craniometric size of crosses of Belgian Blue cattle and Peranakan Ongole was carried out from April to June 2022. The purpose of this study was to determine the distribution and craniometric size of crosses of Belgian Blue cattle and Peranakan Ongole in West Java. This study used 18 crosses of Belgian Blue cattle and Ongole cattle, aged 1 – 9 months. The method used in this research is descriptive exploratory, with census data collection. The variables measured were 11 cranium size parameters consisting of Profile length, Median frontal length, Length of the nasals, Foramen gums length, Condilo basal length, the Greatest breadth of the skull, Least Breadth between the basses of the horn cores, Least frontal breadth, Least breadth between supraorbital foramina, Least breadth between the orbits and Breadth between infraorbital foramina. The results of statistical analysis showed uniform and various coefficients of variation, meaning that the diversity was caused by the effect of heterosis